Community Partnership Empowerment (PKM) Ready-to-drink Teak Leaf Tea Product in Kebontunggul Village, Mojokerto - Tjie Kok; Jocelyne; Richard Meaven; Benedictus Kevin Indarto Ongkowijoyo; Amanda Putri Nahumury; Mangihot Tua Goeltom (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
Kebontunggul Village has significant potential for medicinal herbs that have not yet been fully utilized. This Community Partnership Empowerment (PKM) program aims to strengthen the capacity of BUMDes Gajah Mada in Kebontunggul Village to develop value-added herbal products derived from local resources. The program focuses on improving community knowledge, technical skills, and business management in herbal product development to support sustainable village economic activities. The program was implemented through several integrated activities, including socialization, training, and education on herbal processing, technology implementation for product packaging, and monitoring and evaluation to ensure program sustainability. The primary objective was to develop a ready-to-drink teak leaf tea product while establishing a more systematic stock management system for raw materials and finished products within the BUMDes. The results indicate a substantial improvement in participants’ knowledge, as reflected by the increase in training evaluation scores from 24.3 ± 13.8% before training to 97.2 ± 3.73% after training. The adoption of packaging technology and inventory management practices also enabled BUMDes to initiate the production of ready-to-drink teak leaf tea as a value-added herbal product. These outcomes demonstrate the potential of participatory community empowerment programs to strengthen village-based enterprises and enhance the economic value of local herbal resources